2018
DOI: 10.1002/ajhb.23133
|View full text |Cite
|
Sign up to set email alerts
|

Measuring digit lengths with 3D digital stereophotogrammetry: A comparison across methods

Abstract: Digit measurements and derived ratios from 3D stereophotogrammetry showed high intraobserver agreement (similar to more traditional methods) suggesting that landmarks could be placed reliably on 3D hand surface images. While digit length measurements were found to be comparable across all three methods, ratios derived from direct anthropometry tended to be higher than those calculated indirectly from 2D or 3D images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On the digital image, a line was digitally drawn from the middle of the lowest crease from the index and ring finger to the tip of each finger and the lengths of the lines were measured. The value obtained for second digit was then divided by the value of fourth digit separately for both hands to get 2d:4d (Allaway, Bloski, Pierson, & Lujan, ; Gremba & Weinberg, ). The digit lengths were measured twice independently and the consistency was examined using Cronbach's alpha test.…”
Section: Methodsmentioning
confidence: 99%
“…On the digital image, a line was digitally drawn from the middle of the lowest crease from the index and ring finger to the tip of each finger and the lengths of the lines were measured. The value obtained for second digit was then divided by the value of fourth digit separately for both hands to get 2d:4d (Allaway, Bloski, Pierson, & Lujan, ; Gremba & Weinberg, ). The digit lengths were measured twice independently and the consistency was examined using Cronbach's alpha test.…”
Section: Methodsmentioning
confidence: 99%
“…It was not possible to capture data on the thumb because it was slightly rotated with the hand in the aforementioned posture. Similar landmarks collected from 2D digital scans used in a prior study of finger measurements showed very low error from repeated measures, with intraclass correlation coefficients exceeding 0.97 [ 5 ]. Using x , y coordinates from the collected landmarks, finger widths were calculated at the proximal and distal joints of fingers 2–5 on each hand ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 88%
“…The present sample is focused on adults of recent (self-identified) European ancestry, recruited as either the unaffected relatives of index cases with an orofacial cleft or as unaffected controls. Starting with an initial sample of 754, individuals were excluded if they (1) were affected with a cleft of the lip and/or palate; (2) had missing data; (3) had any reported hand malformations (e.g., syndactyly) or conspicuous trauma or injuries; (4) reported having a genetic syndrome; (5) were over 60 years of age; or (6) reported an ancestry other than European. The upper age cut off was applied to mitigate the potential for age-related joint changes to impact the results [4].…”
Section: Methodsmentioning
confidence: 99%
“…The digital scans were imported into the program tpsDIG2 ( http://sbmorphometrics.org/index.html ) and landmarks were placed on the fifth finger at the midpoint of the metacarpophalangeal crease, the distal interphalangeal joint, and the distal margin of the fingertip ( Fig 1 ). A prior study of landmark-based finger dimensions obtained from digital scans have shown very low error from repeated measures, with intraclass correlation coefficients exceeding 0.97 [ 8 ]. Using x,y coordinates from the collected landmarks, the angle of the distal interphalangeal joint (between the middle and distal phalanges) was calculated to capture the degree of fifth finger radial curvature.…”
Section: Methodsmentioning
confidence: 99%